The Effect of Cost Structure, Liquidity, and Leverage on Financial Distress with Mediating Profitability and Firm Size Control - Priska Putri Parungky; Baldric Siregar; Miswanto; Frasto Biyanto (PT. Anagata Sembagi Education, 2026)
This study examines the relationship between cost structure, liquidity, leverage, profitability, and financial distress in textile and garment companies listed on the Indonesia Stock Exchange. The main focus of the study is directed at two things: assessing the direct influence of cost structure, liquidity, and leverage on financial distress, and examining whether profitability can explain the indirect influence pathways of these financial variables. The study uses a quantitative approach with secondary data sourced from the companies' annual financial reports for the period 2019-2023. Testing is conducted through panel data regression and path analysis, while company size is used as a control variable to ensure that model estimation is not solely influenced by differences in business scale. Conceptually, a rigid cost structure and high leverage are expected to increase financial distress, while liquidity and profitability are expected to weaken the likelihood of financial distress. This study is expected to contribute to the financial distress literature by positioning profitability as a mediating mechanism, particularly in the context of the Indonesian textile industry facing cost pressures, import competition, and weakening financial performance. From a practical perspective, this model can be used as a basis for initial evaluation for management in controlling financial risk through cost efficiency, strengthening cash flow, debt management, and increasing profit-generating ability.